29th Joint Propulsion Conference and Exhibit 1993
DOI: 10.2514/6.1993-2526
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional numerical simulation of gradual opening in a wave rotor passage

Abstract: The evolution of the contact interface and the propagation of compression waves inside a single wave rotor passage gradually opening to and traversing an inlet port is studied numerically using an inviscid formulation of the governing equations. Insights into the response of the interface and kinematics of the flow field to various opening times are given. Since the opening time is inversely proportional to the rotational speed of the rotor, the effects of passage rotation such as centripetal and Coriolis acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…One of the major shifts in the study of wave rotor engines in the recent years is the inclusion of the effect of gradual opening of the wave rotor passage on its operation and performance. Larosiliere [15,16] investigated the effect of speed at which the passages are opened, using numerical methods. His analysis concluded that for long opening times, the interface between inflow and the driven gas in the passage becomes very distorted due to interactions of the multiple reflected compression waves.…”
Section: Numerical and Analytical Study Of Wave Rotorsmentioning
confidence: 99%
“…One of the major shifts in the study of wave rotor engines in the recent years is the inclusion of the effect of gradual opening of the wave rotor passage on its operation and performance. Larosiliere [15,16] investigated the effect of speed at which the passages are opened, using numerical methods. His analysis concluded that for long opening times, the interface between inflow and the driven gas in the passage becomes very distorted due to interactions of the multiple reflected compression waves.…”
Section: Numerical and Analytical Study Of Wave Rotorsmentioning
confidence: 99%
“…There are, however, periods where only a certain portion of the channel is exposed to a port, as shown in Figure 3(a). This gradual passage opening is of paramount importance in the formation of primary shock waves [55]. To account for this, a function is defined that determines the amount of overlap based on port opening and closing positions, channel width and the channel position at each time step.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…The velocity upgrading differential equation of SINS can be simplified as equation (9). Subsequently, the integral operation is performed using Runge-Kutta method, so that the real-time velocity variation can be obtained 26…”
Section: Prediction Model Of Ekf For Quadruped Robotmentioning
confidence: 99%